2014
DOI: 10.1007/s00170-014-6178-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and modeling investigation of surface roughness in end-milling of polyamide 6/multi-walled carbon nano-tube composite

Abstract: Nowadays, Manufacturers tend to use polymer nano-composites as raw material because of their high thermo-mechanical properties and strength to weight ratio. Due to production methods of nano-composites which result in simple cross-sections and rising demands for private products, the need for machining polymers has increased. In this study, the surface roughness of polyamide 6/multi-walled carbon nano-tube composite has been investigated after endmilling. The nano-composite samples were produced with 3.5 wt% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, this Ra value was lower than the CF reinforced PA6 composites. Similarly, while [26], stated that the Ra decrease with CNT addition compared to neat PA6 in their study, [24] found out the increase on PA66 hole quality with the addition of glass fiber whiskers. It was declared that the decrease of Ra was corelated with the heat transformation from drilling region to tool bit and chip [30].…”
Section: Pa6+03 Mwcntmentioning
confidence: 79%
See 1 more Smart Citation
“…However, this Ra value was lower than the CF reinforced PA6 composites. Similarly, while [26], stated that the Ra decrease with CNT addition compared to neat PA6 in their study, [24] found out the increase on PA66 hole quality with the addition of glass fiber whiskers. It was declared that the decrease of Ra was corelated with the heat transformation from drilling region to tool bit and chip [30].…”
Section: Pa6+03 Mwcntmentioning
confidence: 79%
“…On another study according to the findings it is said that tool wear is greater in machining of reinforced Polyamide 6 composite material [25]. [26] investigated the milling of multi-walled carbon nanotube reinforced Polyamide 6 composite. They pointed out the feed rate was most effective parameter on Ra.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Farshbaf Zinati and Razfar [9] numerically modeled FSP of PA 6 to study material flow and strain during FSP. On the other hand, Farshbaf Zinati and Razfar [10] and Farshbaf Zinati et al [11] study machinability of PA 6/MWCNT composite fabricated by FSP. Panneerselvam and Lenin [12] performed FSW on PA 6 to study the effects of FSW parameters on welding quality.…”
mentioning
confidence: 99%